VD_FINDINFO Décision / 2012 / 448 vom 10. Mai 2012 - VD Tribunal cantonal (2012)
INDEMNITÉEN GÉNÉRAL, DÉFENSE D'OFFICE | 132 CPP (CH), 135 al. 2 CPP (CH), 135 CPP (CH), 158 al. 1 let. c CPP (CH), 159 CPP (CH), 395 let. b CPP (CH)